Students' Construction of Conjectures Assisted by GeoGebra for Graphing Linear Equations: Cases of Female Students - Rosyidi, Abdul Haris; Yanti Nur Rahmadhani (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2024)
This study aims to describe female students' conjecture construction on the topic of linear equation graphs with the assistance of GeoGebra. The study involved two female students who had mastered the necessary prerequisite material. Research instruments included conjecture construction tests and interviews, which were analyzed based on these conjecture construction indicators: 1) problem identification and exploration, 2) formulating conjectures, 3) testing and refining conjectures, and 4) proving conjectures. Results showed that, in the problem identification and exploration stage, students identified what was asked in the question, determined the information needed to answer it, and explored examples using GeoGebra. One student independently identified a pattern, while the other required an explanation. In the conjecture formulation stage, both students needed guidance to construct a general conjecture. Both students tested their conjectures, though only one needed to refine it. Initially, proof was conducted through examples; ultimately, both students succeeded in generalizing their proofs.